Effects of climate change on probable maximum precipitation: A sensitivity study over the Alabama‐Coosa‐Tallapoosa River Basin. Issue 9 (5th May 2017) - Rastogi, Deeksha; Kao, Shih‐Chieh; Ashfaq, Moetasim; Mei, Rui; Kabela, Erik D.; Gangrade, Sudershan; Naz, Bibi S.; Preston, Benjamin L.; Singh, Nagendra; Anantharaj, Valentine G.
Abstract: Probable maximum precipitation (PMP), defined as the largest rainfall depth that could physically occur under a series of adverse atmospheric conditions, has been an important design criterion for critical infrastructures such as dams and nuclear power plants. To understand how PMP may respond to projected future climate forcings, we used a physics‐based numerical weather simulation model to estimate PMP across various durations and areas over the Alabama‐Coosa‐Tallapoosa (ACT) River Basin in the southeastern United States. Six sets of Weather Research and Forecasting (WRF) model experiments driven by both reanalysis and global climate model projections, with a total of 120 storms, were conducted. The depth‐area‐duration relationship was derived for each set of WRF simulations and compared with the conventional PMP estimates. Our results showed that PMP driven by projected future climate forcings is higher than 1981–2010 baseline values by around 20% in the 2021–2050 near‐future and 44% in the 2071–2100 far‐future periods. The additional sensitivity simulations of background air temperature warming also showed an enhancement of PMP, suggesting that atmospheric warming could be one important factor controlling the increase in PMP. In light of the projected increase in precipitation extremes under a warming environment, the reasonableness and role of PMP deserve more in‐depth examination. Key Points: Numerical model is able to provide PMP estimates that are comparable to those from a conventional HMR approach The increase of precipitable water versus the increase of PMP depth exhibits a large spread and does not fall near the 1:1 line An increase in the deterministic PMP storm upper bound in a warming environment is projected through two different modeling approaches